18F-FDG PET brain findings in disease-discordant monozygotic mosaic twins with Cri du Chat (5p-) syndrome. Issue 3 (4th May 2021) - Cistaro, Angelina; Schiera, Irene Giovanna; Fania, Piercarlo; Tognon, Fabio; Liava, Alexandra; Danesino, Cesare; Albani, Giovanni; Guala, Andrea; Vogrig, Alberto; Quartuccio, Natale
ABSTRACT: We describe the first report on the genotype-phenotype patterns and [18F] fluoro-deoxygluycose ( 18 F-FDG) Positron Emission Tomography (PET) findings in two disease-discordant monozygotic twins with Cri du Chat syndrome (CdcS) presenting deletion of 5p, 46, XY, del(5)(p14)/46, XY. One twin showed a severe phenotype; significant 18 F-FDG PET hypometabolism (p=0.001) was revealed in the left and right hemispheres, thalamus, cerebellum, and midbrain, whereas hypermetabolism was detected in the left premotor cortex. The other twin presented a mild phenotype; significant hypometabolism was detected only in the right side (parahippoccampal gyrus and cerebellum). Further studies should investigate the causes of phenotypic discordance in twins with CdcS.